Hydrological applications of GIS - Gurnell, A.M. (Angela M.); Montgomery, David R. (Advances in hydrological processes, 1999)
This book deals with the technical problems encountered in hydrological applications of GIS, at scales ranging from the catchment to short river reaches and on a wide range of hydrological processes in both pure and applied contexts.